The Effect of Weigh in Motion Installation on Traffic Volume, Speed and Accident Rate of Goods Vehicles on The Pekanbaru – Dumai Toll Road - Arief Yeri Krisnanto; Aang Gunawan; Primadi Candra Susanto (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to analyze the impact of implementing a Weigh In Motion (WIM) system on the traffic performance of freight vehicles on the Pekanbaru-Dumai Toll Road. The WIM was installed in response to the Circular Letter of the Minister of Transportation No. 116 of 2021 and functions as an automated enforcement technology to prevent Over Dimension Over Load (ODOL) vehicles from entering the toll road. The research method used was a one-group pretest-posttest experimental design with a descriptive-comparative quantitative approach. Secondary data was obtained from the toll road operator (PT Hutama Karya), covering three months before (December 2023 - February 2024) and three months after (March 2024 - May 2024) the WIM installation at four main toll gates. Three performance variables were analyzed: total traffic volume, average speed of freight vehicles, and the number of accidents involving freight vehicles. The analysis results show that after the WIM installation, there were changes with substantial practical significance: (1) total traffic volume decreased by 7.08% (from an average of 72,358 to 67,233 vehicles/month), indicating a filtering effect on ODOL vehicles; (2) the average speed of freight vehicles increased by 10.41% (from 29.88 km/h to 32.99 km/h), as an impact of improved traffic stream homogeneity; and (3) the number of freight vehicle accidents dropped sharply by 50% (from 2.67 to 1.33 incidents/month), with a large effect size (Cohen's d) of 1.155. The study concludes that WIM is effective not only as an enforcement tool but also as a traffic management instrument that creates a beneficial trade-off: a limited reduction in volume is exchanged for increased efficiency and, most importantly, a highly significant improvement in safety. This research recommends the expansion of WIM to other strategic toll road sections and further studies with longer observation periods and quasi-experimental designs.